The role of agricultural insurance in promoting the agricultural sector and achieving economic development, while studying its reality in Algeria. - Farajallah, Ahlem (Finance and Business Economies Review, 2020)
The agricultural sector in the Arab world in general and in Algeria in particular suffers from a number of risks as a result of being subject to many fluctuating natural variables that are impossible to control, which makes the orientation towards establishing agricultural insurance principles in those countries an imperative, because of its great advantages on the economy The national and the agricultural sector alike, in terms of providing the necessary stability and support to the agricultural investor in terms of reducing the risks and dangers to which agricultural production is exposed, both plant and animal, as agricultural insurance guarantees compensation for losses that can occur and the distribution of risks between the various Subscribers, which guarantees the agricultural investor a positive guarantee and incentive to practice the activity and expand their agricultural investments, which is the main step for the path towards selfsufficiency in agricultural products.